Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0300060518765896
|View full text |Cite
|
Sign up to set email alerts
|

The potential mechanism of mitochondrial dysfunction in septic cardiomyopathy

Abstract: Septic cardiomyopathy is one of the most serious complications of sepsis or septic shock. Basic and clinical research has studied the mechanism of cardiac dysfunction for more than five decades. It has become clear that myocardial depression is not related to hypoperfusion. As the heart is highly dependent on abundant adenosine triphosphate (ATP) levels to maintain its contraction and diastolic function, impaired mitochondrial function is lethally detrimental to the heart. Research has shown that mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 116 publications
0
25
0
7
Order By: Relevance
“…Mitochondria seem to play an important role in organ damage during sepsis. 69 Myocardial injury during sepsis leading to LV dysfunction portends a poor prognosis. It has been suggested that the pathophysiology of sepsisinduced cardiac dysfunction may relate to increased oxidative stress, active inflammation, impaired β-adrenergic signaling, enhanced apoptosis, suppression of metabolic pathways, and decreased ATP synthesis in the cardiomyocytes.…”
Section: Sepsis-induced CMmentioning
confidence: 99%
“…Mitochondria seem to play an important role in organ damage during sepsis. 69 Myocardial injury during sepsis leading to LV dysfunction portends a poor prognosis. It has been suggested that the pathophysiology of sepsisinduced cardiac dysfunction may relate to increased oxidative stress, active inflammation, impaired β-adrenergic signaling, enhanced apoptosis, suppression of metabolic pathways, and decreased ATP synthesis in the cardiomyocytes.…”
Section: Sepsis-induced CMmentioning
confidence: 99%
“…The autophagic receptor protein SQSTM1/p62 acts to recognize ubiquitinated mitochondrial proteins and link them, through binding to LC3 to autophagosome (Preau et al, 2016). Damaged mitochondria are isolated by autophagosomes and eventually degraded by fusion with lysosomes, promoting the recovery of septic organ function (Bartz et al, 2015; Pan et al, 2018). Another key transcription factor for mitochondrial quality control is nuclear factor erythroid 2-related factor 2 (Nrf2) (Stępkowski and Kruszewski, 2011).…”
Section: Regulation Of Autophagy In Sepsis and Its Mechanism Of Actionmentioning
confidence: 99%
“…Prompt removal of damaged mitochondria can prevent oxidative damage. Otherwise, oxidative damage may cause apoptosis, leading to worsening of myocardial damage in sepsis (Pan et al, 2018). Beclin-1 promotes mitochondrial biogenesis via PINK1/Parkin as well as AMPK/ULK1, and also selectively facilitates PINK1-Parkin mitophagy for the clearance of damaged mitochondria.…”
Section: Mechanism Of Action Of Autophagy In Different Organsmentioning
confidence: 99%
“…Mitochondria are ubiquitous cellular organelles that are responsible for energy metabolism in eukaryotic cells and have been associated with various conditions, including Alzheimer's disease, Parkinson's disease, diabetes mellitus, various cardiovascular diseases, and lung cancer . Mitochondrial DNA mutations and associated disorders are also related to tumor development, growth, angiogenesis, and metastasis .…”
Section: Introductionmentioning
confidence: 99%